(untitled) (Global Journal of Human-Social Science, 2023)
Changes in soil moisture and temperature can directly influence soil carbon emissions which can add carbon to the atmosphere and make the greenhouse effect more intense In this sense research is needed that contributes to this knowledge and that simulates future scenarios allowing actions to be taken in advance Thus an experiment was set up in which carbon dioxide efflux was collected over a period of one year in three Brazilian biomes Cerrado Pantanal and Cerrado-Amazonian Ecotone and to verify the influence of soil moisture leaf area index and litter multiple regression models were carried out Correlation analyses were performed and subsequently sensitivity analyses were conducted for possible efflux increases owing to 2 C and 10 decreases or increases in soil temperature and moisture respectively simulating possible climate change scenarios The results showed that of the three study areas the Cerrado forest was most resistant to changes in these variables and the correlation between the carbon efflux and the variables soil temperature and moisture were positive and significant for Cerrado and Pantanal